Energy metabolism of rat skeletal muscle modulated by the rate of perfusion flow - Stefl, B; Mejsnar, J A; Janovská, A (Experimental physiology, 1999)
In order to advance our understanding of the phenomenon of flow-induced increases in the metabolism of the relaxed muscle, the metabolic rate of the isolated rat gracilis muscle was investigated at 28 degrees C in vitro. The muscle was perfused with cell-free Krebs-Henseleit bicarbonate buffer containing 5% bovine serum albumin and 5 mM glucose, saturated with a gas mixture of 95% O2 and 5% CO2 and simultaneously superfused with a medium saturated with with a low O2 gas mixture (1% O2, 5% CO2 and 94% N2). Two different perfusion flow rates (0.054 and 0.100 ml min-1) have been used. Their influence on oxygen consumption and lactate production has been measured. After a 100 min perfusion period, the muscle was freeze-clamped and analysed for ATP, phosphocreatine, creatine, lactate, pyruvate, inorganic phosphate and glycogen content. The energy state of the cell and the proportions of glycolytic and mitochondrial fluxes of ATP synthesis were evaluated. During perfusion at the low flow rate of 0.054 ml min-1, the oxygen uptake was 45 +/- 9 nmol min-1 (g wet wt)-1, accompanied by a dominance of anaerobic glycolytic synthesis of ATP over mitochondrial ATP synthesis, even though the total delivery of oxygen to muscle was three times higher than oxygen consumption. Increasing the perfusion flow rate to 0.100 ml min-1 increased the oxygen uptake to 120 +/- 6 nmol min-1 (g wet wt)-1, thus leading to a prevalence of mitochondrial ATP synthesis over glycolytic ATP synthesis. The inner stores of glycogen served as the main substrate of energy metabolism and the role of exogenous substrates in the flow-stimulated increase of oxygen uptake was negligible. The increase in perfusion rate also enhanced the energy state of the muscle fibres, which was expressed either as the creatine charge or as the value of the change of Gibbs free energy of ATP hydrolysis. Data indicate that the change of perfusion flow rate per se, apart from oxygen and exogenous substrate supply, elicits changes in the regulation of energy metabolism within non-contracting skeletal muscle under open microcirculation.
Keywords: adenosintrifosfát; techniky in vitro; Substrate Specificity; aerobióza; Aerobiosis; Lactic Acid; krysa rodu Rattus; zvířata; potkani Wistar; Perfusion; Oxygen; Energy Metabolism; kosterní svaly; kyslík; Adenosine Triphosphate; Cattle; energetický metabolismus; Rats, Wistar; Male; substrátová specifita; perfuze; Muscle, Skeletal; skot; In Vitro Techniques; Rats; Animals; mužské pohlaví; kyselina mléčná